2019
DOI: 10.1186/s12995-019-0225-1
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the gut microbiota of patients with silica-induced pulmonary fibrosis

Abstract: Silicosis resulting from silica exposure is a global occupational disease characterized by severe pathological changes in progressive pulmonary fibrosis. Previous evidence has indicated that dysbiosis of the gut microbiota occurs after environmental dust exposure and is associated with certain diseases. The aims of this study are to elucidate the compositional and functional characteristics of the gut microbiota in early-stage silicosis and to understand their influence on pulmonary fibrosis. We investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…In addition to the above common respiratory diseases, other respiratory disorders, such as ILD, acute respiratory distress syndrome (ARDS), acute lung injury (ALI), and ventilator-associated pneumonia (VAP), also show a certain correlation with the gut microbiota. For example, ILD is characterized by progressive fibrosis and respiratory failure, and changes in the gut microbiota have been reported in patients with silicosis and pulmonary fibrosis [96]. ARDS/ALI is the most common form of organ failure in critically ill patients, and VAP, which is among the most common infections in mechanically ventilated patients, has a high mortality rate [97,98].…”
mentioning
confidence: 99%
“…In addition to the above common respiratory diseases, other respiratory disorders, such as ILD, acute respiratory distress syndrome (ARDS), acute lung injury (ALI), and ventilator-associated pneumonia (VAP), also show a certain correlation with the gut microbiota. For example, ILD is characterized by progressive fibrosis and respiratory failure, and changes in the gut microbiota have been reported in patients with silicosis and pulmonary fibrosis [96]. ARDS/ALI is the most common form of organ failure in critically ill patients, and VAP, which is among the most common infections in mechanically ventilated patients, has a high mortality rate [97,98].…”
mentioning
confidence: 99%
“…1 a). We harvested cells for transcriptomic detection based on our findings from our pilot study that suggested that cell damage at this timepoint could significantly induce EMT [ 29 31 ]. The details of the changes in mRNA expression are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…This may provide evidence for speci c damages to the respiratory tract of the coal miners not coupled to age, smoking or exposure to hazardous occupational factors. Recently, an increased level of Lachnospiraceae and Lachnoclostridium was reported in patients with silicosis, albeit in the gut microbiome [40].…”
Section: Discussionmentioning
confidence: 99%